Foreign Fighters in the Ukrainian Armed Conflict: An International Humanitarian Law Perspective - Gunawan, Yordan; Ghiyats Amri Wibowo; Arumbinang, Mohammad Hazyar (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2023)
This study discusses foreign fighters who take part in the Ukrainian armed conflict. The aim of this study is to know about the history of the armed conflict of Ukraine, study the relevance of International Humanitarian Law to foreign fighters, and study the implementation of Human Rights obtained by foreign fighters based on International Humanitarian Law. The used is juridical-normative legal research or also called document research with secondary data as the main source. Researchers conduct legislative studies to see synchronization between legislation. Data were collected using literature review techniques, such as perusing, analyzing, and drawing conclusions from relevant documents. The results of this study conclude, first, the history of the Ukrainian armed conflict starting from the independence of Ukraine and culminating in the Russian special military operation that occurred on February 24, 2022. Second, the relevance of international humanitarian law to foreign fighters has no specific definition describing foreign fighters and only foreign terrorist fighters. Third, the implementation of human rights against foreign fighters is an inviolable or inalienable human right. However, in its implementation there are still many violations that occur in the armed conflict of Ukraine. Several methods are needed to overcome this problem, namely, the need to increase understanding and awareness regarding IHL and human rights, especially for foreign fighters, to all parties and, make policy recommendations regarding clarity of understanding for foreign fighters, which can then be used as a guide for policymakers and practitioners to increase the certainty of humanitarian protection for foreign fighters.